MODERN APPROACHES TO ASSESSING CREDITWORTHINESS IN THE PROCESS OF BANK LENDING TO SMALL AND MEDIUM-SIZED BUSINESSES - Karimova Aziza , Makhomadrizoevna (THE INNOVATION ECONOMY, 2025)
This article discusses issues related to approaches to assessing creditworthiness in the process of crediting small and medium-sized businesses. The known methods of creditworthiness assessment are analyzed and their advantages and disadvantages are revealed. Proposals are given on the development of the lending process and improvement of methods for assessing the creditworthiness of borrowers -small and medium-sized businesses